IMPROVEMENT OF FIRE PROTECTION DURING THE OPERATION OF ELECTRICAL INSTALLATIONS OF THE PRODUCTION PROCESS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The development of technology is accompanied by a continuous increase in the level of electrical energy consumption and the improvement of the equipment used. Electrical energy greatly facilitates and improves human labor and at the same time is a source of potential danger, which can lead to serious consequences.